Future primary school teachers and methods for identifying them - Vakhabova Gulshan Vafakul qizi (Zien Journals, 2025)
This in the article Methodological approaches to the development of aesthetic thinking , various tools and methods statement . It is stated that their basis is the teaching of creative activity and aesthetic concepts, cognitive, emotional-value and activity, each of which has a significant impact on the development of the student's personality, his ability to recognize and apply moral and aesthetic norms in everyday life
Keywords: Aesthetic pleasure; aesthetic taste; Aesthetic education